New high‐throughput endstation to accelerate the experimental optimization pipeline for synchrotron X‐ray footprinting. (20th July 2021) - Jain, Rohit; Abel, Donald; Rakitin, Maksim; Sullivan, Michael; Lodowski, David T.; Chance, Mark R.; Farquhar, Erik R.
Abstract : The design of a new high‐throughput X‐ray footprinting endstation and its application to footprinting experimental optimization is described. Abstract : Synchrotron X‐ray footprinting (XF) is a growing structural biology technique that leverages radiation‐induced chemical modifications via X‐ray radiolysis of water to produce hydroxyl radicals that probe changes in macromolecular structure and dynamics in solution states of interest. The X‐ray Footprinting of Biological Materials (XFP) beamline at the National Synchrotron Light Source II provides the structural biology community with access to instrumentation and expert support in the XF method, and is also a platform for development of new technological capabilities in this field. The design and implementation of a new high‐throughput endstation device based around use of a 96‐well PCR plate form factor and supporting diagnostic instrumentation for synchrotron XF is described. This development enables a pipeline for rapid comprehensive screening of the influence of sample chemistry on hydroxyl radical dose using a convenient fluorescent assay, illustrated here with a study of 26 organic compounds. The new high‐throughput endstation device and sample evaluation pipeline now available at the XFP beamline provide the worldwide structural biology community with a robust resource for carrying out well optimized synchrotron XF studies of challenging biological systems with complex sample compositions.